Assessing and Improving the Quality of Sustainability Reports: The Auditors’ Perspective - Boiral, Olivier (Journal of business ethics, 2019)
This article presents, an analysis of the opinions of assurance providers regarding the quality and the limitations of sustainability reports and their recommendations to improve them using the Global Reporting Initiative (GRI) as a framework. The qualitative content analysis of 301 assurance statements for sustainability reports from mining and energy companies provides a comprehensive view of the main outcomes of the assurance process, including its limitations, the application of the GRI principles and suggestions for improving sustainability reports. Taking into account the perceptions of practitioners a priori well informed on the quality of sustainability reports—namely assurance providers—this paper complements the current literature on sustainability reporting and its assurance, including critical approaches that question the reliability of sustainability reports, stakeholder engagement and the accountability of reporting practices. This study contributes to the debates surrounding the quality of sustainability reports, the added value of assurance statements and the ethical issues underlying the assurance process. It also contains important practical implications for auditors, standardization organizations and stakeholders.